Training Quantity and Reorganization of Equivalence Classes with Children - Cardoso, André Lepesqueur (2019)
The effects of baseline review trials were investigated in the formation, reorganization and reestablishment of equivalence classes. Four children (5-6 years old) were exposed to two conditions (With Review and Without Review of the trained relations before the tests) in different orders. In Phase 1, baseline relations (AB, BC and AD) were trained and relations that showed evidence of equivalence were tested. In Phase 2, only relation AD was reversed and reorganization tests were conducted. In Phase 3, the training and tests conducted in Phase 1 were repeated. For three participants, only in the With Review condition, classes were reorganized, as expected from the reversal training, and were reestablished upon return to baseline.